Discrimination of residual and recyclable household waste for automatic waste separation system - Ahamad, Nurul Nazihah; Mohamad, Sarah Yasmin; Midi, Nur Shahida; Yusoff, Siti Hajar; Abd Rahman, Faridah (IEEE, 2018)
Most of the countries in the world are confronting a gigantic issue of waste management system. Due to the rapid urbanization and increasing population, huge volume of waste is produced year by year. Improper waste management system has created a deep concern among people which lead to disturbance to the environment and human health. In this paper, a fully automated system that discriminate residual and recyclable household waste is proposed. It is shown that the prototype system are able to automatically separate waste into residual and recyclable waste by employing a moisture sensor to sort them into wet (residual) and dry (recyclable) waste. The state of the waste is determined by its resistance to current value and the percentage of water content.